Energy, bio fuels and development : comparing Brazil and the United States - Amann, Edmund; Baer, Werner, 1931-2016; Coes, Donald V., 1943- (Routledge studies in development economics ;, 2011)
This collection examines the important and topical issue of the economic, social and environmental implications of concerted attempts to diversify energy sources away from fossil fuels. The book expertly examines this issue by focussing on the contrasting experiences of two major economies; one developed, and the other a rapidly expanding, emerging market.